2021
DOI: 10.1186/s13567-021-00956-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and characterization of human β-defensin-3 and its analogues and microcin J25 peptides against Mannheimia haemolytica and bovine neutrophils

Abstract: Mannheimia haemolytica-induced bovine respiratory disease causes loss of millions of dollars to Canadian cattle industry. Current antimicrobials are proving to be ineffective and leave residues in meat. Antimicrobial peptides (AMPs) may be effective against M. haemolytica while minimizing the risk of drug residues. Cationic AMPs can kill bacteria through interactions with the anionic bacterial membrane. Human β-Defensin 3 (HBD3) and microcin J25 (MccJ25) are AMPs with potent activity against many Gram-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…While data on the effect of Lm -derived formyl peptides on bovine PMN chemotaxis is lacking, available data on the chemotactic effect of E. coli -derived fMLP toward bovine PMN is contradicting. Some authors reported a chemotactic effect of fMLP [ 53 55 ], while others, in line with our results, failed to identify a bovine PMN migratory response toward bacterial peptides (formylated and non-formylated), bacterial culture supernatants, and viable or sonicated Gram-positive and Gram-negative bacteria [ 50 – 52 ]. The latter studies and our findings are supported by the reported lack of FPRs on bovine PMNs [ 52 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While data on the effect of Lm -derived formyl peptides on bovine PMN chemotaxis is lacking, available data on the chemotactic effect of E. coli -derived fMLP toward bovine PMN is contradicting. Some authors reported a chemotactic effect of fMLP [ 53 55 ], while others, in line with our results, failed to identify a bovine PMN migratory response toward bacterial peptides (formylated and non-formylated), bacterial culture supernatants, and viable or sonicated Gram-positive and Gram-negative bacteria [ 50 – 52 ]. The latter studies and our findings are supported by the reported lack of FPRs on bovine PMNs [ 52 ].…”
Section: Discussionsupporting
confidence: 86%
“…To select an effective positive control for PMN chemotaxis, we tested bovine PMN chemotaxis towards bovine IL-8 and fMLP, using, for the latter, concentrations reported to efficiently elicit chemotaxis of human and murine PMN (i.e., 0.1 and 1 µM) [ 45 , 47 , 48 ]. While bovine IL-8 has been shown to strongly elicit bovine PMN chemotaxis [ 49 ], studies on the chemotactic effect of fMLP are contradictive with some indicating that bovine PMN do not migrate towards formyl peptides [ 50 – 52 ], while others claim a chemotactic effect of fMLP on bovine PMN [ 53 55 ]. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HBD3 is an important AMP involved in protection against bacterial and viral infections, and is also known to have immunomodulatory functions ( 20 ). Regarding its antibacterial effects, studies have shown significant bactericidal activity of HBD3 against different G+ve and G-ve bacteria and this may be related to the cationic charges of HBD3 molecules ( 30 , 31 ). Additionally, high expression of HBD3 significantly enhanced wound closure in diabetic animal models infected with Staphylococcus aureus ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitek 2 ® System compact (BioMériuex Available at www.veterinaryworld.org/Vol.15/December-2022/25.pdf SA, USA) was used for identification. Culture plates were grown at 37°C in a rotatory shaking incubator for 16 h [17,18]. About 30 colonies of pure bacteria were transferred into 250 mL of brain heart infusion broth (Oxoid).…”
Section: Preparation Of Experimental Adjuvant and Vaccinesmentioning
confidence: 99%